Studying the Possibility of Mullā Hadi Sabzevari’s Thought of Being New Sadrāi - Hasan Abasi Hoseinabadi (حکمت صدرایی, 2013)
Modernization has occurred in philosophical discourses of New Sadrāi in form, method and content. Changes and modernization also have occurred in the philosophy of Mullā Hadi Sabzevari in relation with these issues. Accordingly, we introduce him as initiator of the philosophical movement of New Sadrāi. Although his thought is in the line of Sadrāi Philosophy, there are some disagreements between them. Besides, there are some innovations in Sabzevari's thoughts. Regarding social and historical conditions, he uses the logic and the style of Sharhe Manzoomeh in explaining philosophical issues to the public through logic and poetry. This represents a novelty in the structure of his thought. While Mullā Sadrā had not spoken about logic, Mullā Hadi Sabzevari has devoted a major part of his book to logic. There are some differences between Mullā Sadrā's ideas and Sabzevari's ones on epistemology, unity of intellect and intelligible, composition of matter and form, perception of universals, creation and … . Accordingly, I shall investigate the changes in Sabzevari’s thought, and give reasons for introducing him as the initiator of the New Sadrāi movement, a movement to which Tabatabai gave the strength.